Methionine Supply During Late-Gestation Triggers Offspring Sex-Specific Divergent Changes in Metabolic and Epigenetic Signatures in Bovine Placenta. Issue 1 (4th January 2019) - Batistel, Fernanda; Alharthi, Abdulrahman S; Yambao, Rainie R C; Elolimy, Ahmed A; Pan, Yuan-Xiang; Parys, Claudia; Loor, Juan J
ABSTRACT: Background: Nonruminant male and female offspring respond differently to gestational nutrition, with placenta contributing to the underlying mechanisms. However, similar data are lacking in large ruminants. Objectives: The aim of this study was to investigate the impact of methionine supply during late-gestation on metabolism and DNA methylation in placenta from cows carrying male or female calves. Methods: During the last 28 d of pregnancy, cows were individually fed a control diet (CON) or the control diet plus rumen-protected d, l -methionine (MET; 0.9 g/kg dry matter intake). Placentomes collected at term were classified according to cow dietary treatment and offspring sex as follows: Male CON ( n  = 7), Male MET ( n  = 7), Female CON ( n  = 8), and Female MET ( n  = 8). Calf growth was measured until 9 wk of age. Targeted metabolomics, RT-PCR, global DNA methylation, and activity of selected enzymes in one-carbon metabolism and transsulfuration pathways were performed. Statistics were conducted via ANOVA using MIXED models. Results: At birth, Male MET calves were heavier than Male CON calves (7.6%, P  = 0.02), but body mass was similar at 9 wk of age. In contrast, compared with Female CON, Female MET calves had greater body mass at 9 wk of age (6.3%, P  = 0.03). Compared with Male CON, placenta from Male MET calves had greater concentrations of tricarboxylic acid (TCA) cycle and transsulfuration intermediates (23–100%, P  < 0.05), along with greater 5-methyltetrahydrofolatehomocysteine methyltransferase activity (67%, P  = 0.03). Compared with Female CON, placenta from Female MET calves had greater concentrations of one-carbon metabolism intermediates (13–52%, P  < 0.05). DNA methyltransferase 3A ( DNMT3A ) was upregulated (43%, P  < 0.01) in placenta from Female MET compared with Female CON calves. Global DNA methylation was lower in placenta from Female MET compared with Female CON calves (45%, P  = 0.06). Conclusions: Methionine supply affects placental metabolism, DNA methylation, and body mass of the calf in a sex-specific manner, underscoring its importance as dietary methyl-donor for pregnant cows.